To think the imaginary: a brief reading by Gilbert Durand (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Gilbert Durand sets us in "motion"; showing us that everything is everchanging. He puts us on a fast track going from reflex knowledge to fantasy world through epistemological subversión, boosting knowledge that encompasses everything. Mythologies show us Gods that are demoted to animal state and humans that move up to angelism. Thanks to The antropological structures, (1984) an extensive analysis framework is set up. This framework helps understand, through semantics of attributes and verbs of various short stories, some forms of symbolisation according to geographies, as well as, distinctive ways ofexperiencing death. Similarly, linear and cyclic times coprrespond to various ways to envision Nature and Gods different ways which constitute an x-ray of cultures.The universality of imagination thus presented charms us with a way to delight once again the world.
Keywords: Imagination; image; knowledge; symbols; structures; time